Re-wiring the ancient novel - Cueva, Edmund P., 1964- (Ancient narrative. Supplementum, 2018)
The Fifth International Conference on the Ancient Novel, which was held in Houston, Texas, in the fall of 2015, brought together scholars and students of the ancient novel from all over the world in order to share new and significant developments about this fascinating field of study and its important place in the field of Classical Studies. The essays contained in these two volumes are clear evidence that the ancient novel has become a valuable part of the Classics canon and its scholarly attempts to understand the ancient Graeco-Roman world.